Discussion - Of Mr. Brown's Paper or1 The Vein-System of the Standard Mine, Bodie. California (see Trans.. xxxviii., 343) (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1909)
H. W. Turner, Portland, Ore. (communication to the Secretary*) :—Mr. Brown's paper on the complicated groups of veins exposed in the workings of the Bodie mine forme a valuable contribution to the literature of the structural features of ore-depoeits. It is much to be desired that managers should put into print the results of their observations of the mines under their charge. These observations, as well as data of production, kind of ores, etc., usually accumulate for years, and unless the mining geologists of the Geological Survey happen along before the mine is worked out, such data seldom get into print. About the year 1899 I went through the mines at Bodie with R. C. Turner, then superintendent, and made some notes on the veins and gangue-minerals, and collected some specimens. Mr. Brown refers to crystals of feldspar (albite) found on fragments of quartz on the surface. I collected a number of specimens of these crystals, mostly from Queen Bee hill, and